2018
DOI: 10.9734/afsj/2018/41103
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Awareness on Food Fortification among Mother/Child Caretakers of Kinondoni Municipality, Tanzania

Abstract: Objective: The objective of the study was to evaluate the success of social mobilization and capacity building efforts done to educate the Mother/Child Caretakers and the general public regarding food fortification and the importance of consuming fortified food products in Kinondoni municipality. Methodology:The study involved Mother/Child Caretakers with children aged 6-59 months who were present during the period of the interview at Sinza hospital (n = 26), Magomeni hospital (n = 39), Manzese dispensary (n =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 9 publications
0
0
0
Order By: Relevance
“…Similarly, the results from our study showed that 70% of the respondents answered that they knew that food fortification helps to reduce malnutrition, indicating that the majority of caretakers attending immunization in Nakasongola Health Center IV are aware of the potential benefits of fortified food possibly obtained from nutrition education by the health persons at the health center. This finding is similar to the results from the study by (Kasankala et al, 2018), which found that 68.2% of mother/child caretakers in Kinondoni Municipality, Tanzania knew that food fortification is used to prevent malnutrition.…”
Section: Knowledge Of the Caretakers Of Children About Food Fortifica...supporting
confidence: 89%
“…Similarly, the results from our study showed that 70% of the respondents answered that they knew that food fortification helps to reduce malnutrition, indicating that the majority of caretakers attending immunization in Nakasongola Health Center IV are aware of the potential benefits of fortified food possibly obtained from nutrition education by the health persons at the health center. This finding is similar to the results from the study by (Kasankala et al, 2018), which found that 68.2% of mother/child caretakers in Kinondoni Municipality, Tanzania knew that food fortification is used to prevent malnutrition.…”
Section: Knowledge Of the Caretakers Of Children About Food Fortifica...supporting
confidence: 89%